2013
DOI: 10.1063/1.4773918
|View full text |Cite
|
Sign up to set email alerts
|

Space charge suppression induced by deep traps in polyethylene/zeolite nanocomposite

Abstract: Nanoparticle surface modification induced space charge suppression in linear low density polyethylene Appl. Phys. Lett. 95, 242905 (2009); 10.1063/1.3275732 Significant suppression of space charge injection into linear low density polyethylene by surface oxyfluorination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 8 publications
5
54
0
Order By: Relevance
“…1,2 Generally, it is difficult for charge carriers to escape from the deep trap sites, due to the higher potential barrier, especially for nanodielectrics with high loading concentration, which is inconsistent with the observed conductivity phenomenon. The quantum tunneling mechanism based on the percolation theory has been investigated in black carbon and carbon nanotube polymer Electronic addresses: gc@ecs.soton.ac.uk and sli@mail.xjtu.edu.cn composites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Generally, it is difficult for charge carriers to escape from the deep trap sites, due to the higher potential barrier, especially for nanodielectrics with high loading concentration, which is inconsistent with the observed conductivity phenomenon. The quantum tunneling mechanism based on the percolation theory has been investigated in black carbon and carbon nanotube polymer Electronic addresses: gc@ecs.soton.ac.uk and sli@mail.xjtu.edu.cn composites.…”
mentioning
confidence: 99%
“…1,2 However, the effect of space charge suppression has a strong link with the nanoparticle concentration. For low loading concentration, the charge suppression can be observed clearly by the pulsed electroacoustic method (PEA), while charge transport behavior becomes more complicated for high loading concentration.…”
mentioning
confidence: 99%
“…TSC measurement has also confirmed the formation of deep trap after introducing nanoparticles as the TSC peak shifts from a lower temperature towards a higher temperature after introducing nanofillers [6].…”
Section: B Deep Traps and Evidencesmentioning
confidence: 76%
“…The results indicate that the peaks of the trap levels are in the range of 0.95-1.00 eV, which are assumed to be deep trapping sites and agree well with the previous results. (16,17) The , respectively. It is also shown that there are much fewer trapping sites in LD-S than in the other two groups, which might be related to the uniform cell size and the smaller crystal-amorphous interfacial regions.…”
Section: Effect Of Annealing Rate On Charge Injection and Transportmentioning
confidence: 99%